Ciz1 is a novel predictor of survival in human colon cancer. (July 2014) - Wang, Dong-qing; Wang, Kun; Yan, Dong-wang; Liu, Ju; Wang, Bin; Li, Ming-xue; Wang, Xiao-wei; Liu, Jing; Peng, Zhi-hai; Li, Guang-xin; Yu, Zhen-hai
Cip1-interacting zinc-finger protein1 (Ciz1) is a nuclear matrix protein associated DNA replication factor which has been implicated in breast and lung cancer progression. However, the clinical significance of Ciz1 expression in colon cancer has not been determined. This study aimed to examine Ciz1 expression pattern and its potential as a biomarker of prognosis in colon cancer. Using quantitative PCR, tissue microarray (TMA), and ELISA, we evaluated Ciz1 mRNA and protein levels in tumor tissues from patients with colon cancer and in paired adjacent normal tissues. Ciz1 mRNA expression was significantly upregulated in 22 of 39 paired samples ( P < 0.001). Immunohistochemistry on TMA-containing samples from 203 colon cancer patients indicated that Ciz1 protein expression was significantly higher in tumor tissues than in adjacent normal tissues (Stuart-Maxwell test, P < 0.001). Elevated expression of Ciz1 protein was significantly correlated with T stage ( P < 0.001), N stage ( P = 0.005), M stage ( P = 0.021), and AJCC stage ( P = 0.002). Multivariate Cox proportion hazard model analysis revealed that Ciz1 expression is an independent prognostic factor for overall time (OS; hazard ratio (HR): 1.76; 95% confidence interval (CI): 1.04–2.98; P = 0.034) and disease-free survival (DFS; HR: 2.02; 95% CI: 1.14–3.58; P = 0.017) of patients with colon cancer after colectomy. Our data suggested that Ciz1 may be involved in colon cancer progression and could serve as a novel predictor of survival for colon cancer patients.